Occurrence of epizoic encrustation on Thenus orientalis (Lund) from south west coast of India - Ramachandran, S; Philip, K K; Narayanan, M; Tharumar, Y (Indian Journal of Fisheries, 2011)
The incidence of epizoic encrustation on Thenus orientalis by the cirriped,Octolasmis warwickii from south west coast (Lat. 10Â° 24'N Long. 75Â° 45'E) at adepth of 48 m is reported with reference to similar findings elsewhere.